2013
DOI: 10.4049/jimmunol.1202472
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like Activity of High-Mobility Group Box 1 Protein and Its Role in Reducing the Formation of Polyglutamine Aggregates

Abstract: High-mobility group box 1 protein (HMGB1), which mainly exists in the nucleus, has recently been shown to function as a sentinel molecule for viral nucleic acid sensing and an autophagy regulator in the cytoplasm. In this study, we studied the chaperone-like activity of HMGB1 and found that HMGB1 inhibited the chemically induced aggregation of insulin and lysozyme, as well as the heat-induced aggregation of citrate synthase. HMGB1 also restored the heat-induced suppression of cytoplasmic luciferase activity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Notably, a new study has identified HMGB1 as a chaperone-like molecule, which interacts with polyglutamine (polyQ) and reduces aggregation and toxicity of polyQ, the pathogenic cause of Huntington disease. 29 The finding, together with the previous report that HMGB1 interacts with SNCA filaments in PD brain samples, 21 revealed a possible connection between HMGB1 and the pathogenic protein aggregates associated with neurodegenerative diseases including PD and Huntington disease. Meanwhile, SNCA and polyQ have been shown to impair autophagy, without a fully understood mechanism.…”
Section: Discussionsupporting
confidence: 59%
“…Notably, a new study has identified HMGB1 as a chaperone-like molecule, which interacts with polyglutamine (polyQ) and reduces aggregation and toxicity of polyQ, the pathogenic cause of Huntington disease. 29 The finding, together with the previous report that HMGB1 interacts with SNCA filaments in PD brain samples, 21 revealed a possible connection between HMGB1 and the pathogenic protein aggregates associated with neurodegenerative diseases including PD and Huntington disease. Meanwhile, SNCA and polyQ have been shown to impair autophagy, without a fully understood mechanism.…”
Section: Discussionsupporting
confidence: 59%
“…HMGB1-mediated autophagy increases chemoresistance in cancer cells, including colon cancer, pancreatic cancer, osteosarcoma, leukemia, gastric cancer, and ovarian cancer (Huang et al, 2012a; Kang et al, 2010; Liu et al, 2011c; Livesey et al, 2012b; Yang et al, 2012e; Zhan et al, 2012; Zhang et al, 2012d; Zhao et al, 2011a). In addition, HMGB1-mediated autophagy in vitro and/or in vivo prevents polyglutamine aggregates in Huntington’s disease (Min et al, 2013), systemic inflammation during sepsis (Hagiwara et al, 2012; Yanai et al, 2013), N-methyl-D-aspartate-induced excitotoxicity (Perez-Carrion and Cena, 2013), hepatic ischemia-reperfusion injury (Fang et al, 2013b; Shen et al, 2013), and sustains T cell survival in myositis (Zong et al, 2014). Conditional knockdown of HMGB1 in the liver or heart cannot change baseline autophagy level and mitochondrial quality (Huebener et al, 2014).…”
Section: Hmgb1 and Cell Death (Figure 12)mentioning
confidence: 99%
“…S33025, Molecular Probes, Invitrogen) and the cells were washed three times with PBS. The cover slips were mounted on glass slides with mounting medium [29] and observed using a confocal microscope (Olympus Inc., Center Valley, PA, USA). The integrated optical density (IOD) of every imaged RAW264.7 cell was determined using the Image-Pro Plus 5.0 software (Media Cybernetics, Inc., Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%